Proton pump inhibitors are associated with accelerated development of cirrhosis, hepatic decompensation and hepatocellular carcinoma in noncirrhotic patients with chronic hepatitis C infection: results from ERCHIVES. Issue 2 (3rd November 2017) - Li, D. K.; Yan, P.; Abou‐Samra, A‐B.; Chung, R. T.; Butt, A. A.
Abstract : Linked Content This article is linked to Macnaughtan and Jalan paper. To view this article visithttps://doi.org/10.1111/apt.14431 . Summary: Background: Proton pump inhibitors are among the most commonly prescribed medications in the United States. Their safety in cirrhosis has recently been questioned, but their overall effect on disease progression in noncirrhotic patients with chronic liver disease remains unclear. Aim: To determine the impact of proton pump inhibitors on the progression of liver disease in noncirrhotic patients with hepatitis C virus (HCV) infection. Methods: Using the electronically retrieved cohort of HCV‐infected veterans (ERCHIVES) database, we identified all subjects who received HCV treatment and all incident cases of cirrhosis, hepatic decompensation and hepatocellular carcinoma. Proton pump inhibitor use was measured using cumulative defined daily dose. Multivariate Cox regression analysis was performed after adjusting univariate predictors of cirrhosis and various indications for proton pump inhibitor use. Results: Among 11 526 eligible individuals, we found that exposure to proton pump inhibitors was independently associated with an increased risk of developing cirrhosis (hazard ratio [HR]: 1.32; 95% confidence interval: [1.17, 1.49]). This association remained robust to sensitivity analysis in which only patients who achieved sustained virologic response were analysed as well as analysis excluding those with alcohol abuse/dependence. Proton pump inhibitor exposure was also independently associated with an increased risk of hepatic decompensation (HR: 3.79 [2.58, 5.57]) and hepatocellular carcinoma (HR: 2.01 [1.50, 2.70]). Conclusions: In patients with chronic HCV infection, increasing proton pump inhibitor use is associated with a dose‐dependent risk of progression of chronic liver disease to cirrhosis, as well as an increased risk of hepatic decompensation and hepatocellular carcinoma.